2020
DOI: 10.1186/s12014-020-9268-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative site- and structure-specific N-glycoproteomics characterization of differential N-glycosylation in MCF-7/ADR cancer stem cells

Abstract: Background: Cancer stem cells (CSCs) are reported to be responsible for tumor initiation, progression, metastasis, and therapy resistance where P-glycoprotein (P-gp) as well as other glycoproteins are involved. Identification of these glycoprotein markers is critical for understanding the resistance mechanism and developing therapeutics. Methods: In this study, we report our comparative and quantitative site-and structure-specific N-glycoproteomics study of MCF-7/ADR cancer stem cells (CSCs) vs. MCF-7/ADR cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…and CSC N-glycosylation markers (centrosome-associated protein 350 CE350, zinc finger protein GLI1, CD63 antigen and CD13 etc.) were reported in our previous studies (Wang et al 2020b;Xu et al 2020).…”
Section: Intact N-glycoproteins Associated With Cancer Stem Cells (Cscs)supporting
confidence: 73%
See 3 more Smart Citations
“…and CSC N-glycosylation markers (centrosome-associated protein 350 CE350, zinc finger protein GLI1, CD63 antigen and CD13 etc.) were reported in our previous studies (Wang et al 2020b;Xu et al 2020).…”
Section: Intact N-glycoproteins Associated With Cancer Stem Cells (Cscs)supporting
confidence: 73%
“…In comparison of DEGPs in MCF-7 CSCs (relative to MCF-7 cells) (Wang et al 2019) with those in MCF-7/ADR CSCs (relative to MCF-7/ADR cells) (Xu et al 2020), intact N-glycopeptide SLSNSTAR_N2H5F0S0 (P50454, SERPH_ HUMAN, N120) showed the same up-regulation with ratios of 4.23 ± 0.71 and 3.80 ± 0.55, respectively. We found that the expression level of intact N-glycopeptides SLSN-STAR_N2Hx (x = 5-9) was decreased progressively from up-regulation to down-regulation in MCF-7/ADR CSCs (relative to MCF-7/ADR cells) (Xu et al 2020).…”
Section: Intact N-glycoproteins Associated With Cancer Stem Cells (Cscs)mentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, hypersialylation in cancer cells promotes cell migration (18) and apoptosis resistance (19), which lead to tumor growth and poor prognosis (16). CSCs may be further distinguished from differentiated cancer cells by the expression of carbohydrate antigens (20,21), and the Nglycosylation of glycoproteins of CSCs has been related to drug resistance mechanisms (22). Besides, abnormal glycosylation has been shown to regulate signaling pathways and markers involved in conservation of CSCs, such as EpCAM glycosylation on cell adhesion (23) and EMT in breast cancer, or N-glycosylation on MAPK and PI3/Akt pathway (24).…”
Section: Introductionmentioning
confidence: 99%